Mitral isthmus conduction block: intriguing result of radiofrequency catheter ablation for a left concealed accessory pathway - Bulava, Alan; Hanis, Jiri; Sitek, David (Europace, 2010)
We report on our experience with complete mitral isthmus conduction block achieved inadvertently during radiofrequency (RF) catheter ablation for a left lateral concealed accessory pathway (AP) mimicking concentric retrograde activation. This rare condition should be acknowledged to avoid misdiagnosis of another concomitant AP and to avoid RF applications in inappropriate areas.
Keywords: katetrizační ablace; převodní systém srdeční; Atrial Function, Left; Catheter Ablation; srdce - funkce levé síně; ženské pohlaví; dospělí; Humans; Mitral Valve; Adult; srdeční blokáda; Female; kardiostimulace umělá; Heart Conduction System; lidé; Heart Block; Cardiac Pacing, Artificial; mitrální chlopeň